(untitled) (Research, Society and Development, 2020)
Regarding its methodology, the study in question is characterized by being an exploratory study of integrative literature review. Public administration over the past few years has been the target of several criticisms by the media and the population in general, mainly due to cases of public mismanagement. The main cause of this is inefficient or non-existent project management. With the implementation of project management, which is properly planned, observed, directed and controlled, the tendency is for Public Administration, to gradually be able to control fiscal holes, as well as modernizing the way in which it delivers its services to the population. A municipality that has already adopted the practice and target of this study is Niterói. From this, the research question is: how can project management help Public Administration at the same time, control the leakage of the immense public debts they have and deliver basic quality services to the population? Thus, the objective of the study is to carry out a superficial analysis of the situation in the municipality of Niterói after the implementation by law of a project management office in its administration. In general, it was possible to verify that the municipality has already achieved important developments, among which an improvement in the tax issue stands out, as well as the implementation of important works that benefit the urban mobility of citizens.